Impact of the Alphabet Strategy on Improving Diabetes Care at a Free Health Clinic. Issue 4 (2nd October 2019) - Robinson, Jamie; Lang, Betty; Clippinger, David
ABSTRACT: The complexity and cost of diabetes care are barriers to a free health clinic attempting to provide quality care to uninsured patients. The alphabet strategy intervention was selected to increase the number of patients with diabetes receiving care according to the American Diabetes Association guidelines because it is simple and cost-effective. The project results revealed statistically significant increases in clinic uptake of diabetes education, blood pressure interventions, proteinuria, glucose control measurement and intervention, eye exams, and foot exams. The findings may be useful to other free health clinics attempting to provide quality care to their patients with diabetes.